Media Pembelajaran Bahasa Jawa Materi Cerita Rakyat Dengan Metode Demonstrasi Berbasis Multimedia - Fani Danau Innalita; Edy Siswanto (JURNAL TEKNIK INFORMATIKA DAN MULTIMEDIA, 2021)
Based on the results of observations, the learning method used in SMP Negeri 35 Semarang is in the form of lectures, discussions, questions and answers using book media. The learning methods that have been applied so far have not had enough impact on the level of students' understanding of the material taught by the teacher. The method used was less successful due to lack of visualization so students felt bored and bored. This research offers a solution to the use of multimedia with demonstration methods through interesting learning media where media through computers can display images, text, audio and video so that folklore can be more visualized and attract students as well as the learning process can be fun. This study uses the Research and Development (R n D) product development method using 6 of the 10 research stages. The results of the study show that from the media expert validation test, material validation test and user validation test results, the product can be said to be effective and feasible to use.